Path dependency and convergence of three worlds of welfare policy during the Great Recession: UK, Germany and Sweden. Issue 1 (2nd January 2017) - Kiess, Johannes; Norman, Ludvig; Temple, Luke; Uba, Katrin
Abstract : This paper investigates policy responses to the Great Recession in Sweden, the United Kingdom and Germany. Faced with the global financial crisis in 2007, responses in the respective countries differed considerably and followed the "old" paths of their institutional legacies. We focus on labour market and social welfare policies and demonstrate how these differing responses were shaped by path-dependent ideational paradigms. Since these paradigms are first and foremost carried by policy communities, the analysis does not, in contrast to prior studies, only rely on policy documents but outlines the process as seen from the perspective of key public officials and experts in the respective fields. The paper shows how the crisis was perceived and which kinds of arguments were used for explaining the liberal (UK), conservative (Germany) and social–democratic (Sweden) responses to crisis.